Multi‐approach characterization of shallow‐water carbonates off Minamitorishima and their depositional settings/history. (13th April 2021) - Aftabuzzaman, Md.; Yomogida, Kazuki; Suzuki, Shota; Takayanagi, Hideko; Ishigaki, Akimasa; Machida, Shiki; Asahara, Yoshihiro; Yamamoto, Koshi; Hirano, Naoto; Sano, Shin‐Ichi; Chiyonobu, Shun; Bassi, Davide; et al.
Abstract: Sedimentological, geochemical, and chronological analyses were carried out on 18 carbonate rock samples collected at depths of 938, 1085, and 3354 m on the western slope of Minamitorishima (Marcus Island), which is located near the western margin of the Pacific Plate. Four groups of carbonate rocks were distinguished: a mollusk‐rich limestone, a coral‐rich dolomite, a foraminiferal‐nannofossil packstone, and a phosphatized mudstone/wackestone. The mollusk‐rich limestone is characterized by the dominance of bivalves (including rudists) and gastropod shells. Strontium isotope ratios ( 87 Sr/ 86 Sr) and Mesorbitolina ex gr. texana (a large benthic foraminifer) indicate that the shallow‐water carbonates were deposited during the late Aptian–early Albian (ca. 123–111 Ma). The coral‐rich dolomite is characterized by abundant scleractinian corals and nongeniculate coralline algae associated with encrusting acervulinid foraminifers. The biotic composition is similar to that of the Oligocene–Pleistocene carbonates reported from other seamounts in the northwestern Pacific. Geochemical data show that the coral‐rich carbonates were dolomitized at 9.5–6.8 Ma (Tortonian–Messinian) and that normal seawater was the most likely parent fluid. The foraminiferal‐nannofossil packstone is a semi‐consolidated foraminiferal‐nannofossil ooze and was deposited during the Pleistocene (0.99–0.45 Ma). The phosphatized mudstone/wackestone is marked by the absence of macrofossils and the presence of traces of planktic foraminifers. Although its depositional age is not constrained, the Sr isotope ratios indicate that the phosphatization occurred at 33.2–28.9 Ma. After the deposition of the Cretaceous shallow‐water carbonates, including the mollusk‐rich limestone, Minamitorishima was drowned and its top was covered with a pelagic cap, represented by the mudstone/wackestone. The late Eocene–early Oligocene volcanism (40.2–33.2 Ma) caused episodic uplift and returned the top of Minamitorishima to a shallow‐water environment. After the early Oligocene phosphatization of the pelagic cap, coral reefs flourished on the top of this island. The reef limestone was dolomitized during the Tortonian–Messinian.